Magnetic resonance imaging changes of the navicular bursa following navicular bursoscopy in seven horses. (5th August 2020) - Hoaglund, E. L.; Barrett, M. F.
Summary: Navicular syndrome is a multifactorial disease process in horses with multiple structures in the foot contributing to lameness. Surgical debridement is a treatment option for lesions of the navicular bursa and deep digital flexor tendon. This retrospective case series describes the magnetic resonance imaging (MRI) appearance of the navicular bursa following bursoscopy. Seven horses (three being bilaterally affected) with forelimb lameness isolated to the foot, and pre‐ and post‐operative MRI were included. All limbs had concurrent lesions associated with the deep digital flexor tendon, navicular bone, impar ligament, collateral sesamoidean ligament and/or distal interphalangeal joint. All bursae developed or had progression of proliferative bursal tissue following surgery. At recheck MRI, following rehabilitation protocols, almost all horses had improved to resolved lameness with relatively unchanged concurrent lesions despite the navicular bursa appearance worsening. Outcomes for return to work were poor with only two horses going back to the previous level of work.